Optimal Placement of Viscoelastic Layers in Sandwich Beams for Maximum Vibration Attenuation and Minimum Creep Deflections (Journal of Civil Engineering Researchers, 2025)
Until now, various mathematical models have been proposed to characterize the behavior of viscoelastic materials and facilitate their implementation in finite element software. However, it remains unclear which configuration of the viscoelastic layer along the thickness and length of the beam yields the lowest creep deflection and highest damping effect under applied forces. To fill this literature gap, efforts are undertaken in this study to identify the optimal placement of the viscoelastic layers in the sandwich beam. To reach this aim, the creep and dynamic behaviors of sandwich beams with different boundary conditions and various configurations of the viscoelastic layer along the thickness and length were investigated using a finite element model. The obtained results indicate that the damping capability and creep deformations of the sandwich beam are strongly affected by the position of the viscoelastic layers.
Keywords: Sandwich Beams; Viscoelastic Layers; Vibration Attenuation; Optimal Position; Finite Element